Configuration Synthesis and Performance Analysis of Reconfigurable Decoupled Parallel Mobile Robots - Pan Wuxing; Li Ruiqin; Ning Fengping; Li Yanlong; Feng Xiaodong (Jixie chuandong)
To improve the carrying capacity of the robot, reduce the energy consumption of the driving motor and make the wheel-leg mode switching smooth and efficient, a reconfigurable decoupled parallel mobile robot configuration is proposed, and the configuration synthesis research and decoupling and singularity analysis are carried out. According to the expected degree of freedom of the robot's mechanical leg, four main motion limbs are synthesized. The 58 constraint limbs are synthesized based on the de-constraint method of the screw theory. Based on the virtual chain method of the screw theory, the 3R spherical parallel mechanism is synthesized as the bearing limb of the mechanical leg. Then two robot examples are given. Taking one of the robots as an example, the input-output equation is established, and the decoupling of the mechanical leg is analyzed. The singular configuration of the reconfigurable unit is verified by the reduction to absurdity, and the singular type is judged based on Grassmann line geometry. Finally, the influence of the singularity of the bearing limb on the motion output of the mechanical leg is analyzed. The mechanical leg of the robot adopts a parallel limb chain configuration, which has strong bearing capacity. The robot realizes wheel-leg switching based on constraint singularity, which makes the switching action more stable. The configurability of the mechanical leg reduces the energy consumption of the drive motor. Each drive of the mechanical leg is decoupled from the other, which reduces the control difficulty and makes the wheel-leg mode switching of the mechanical leg more efficient.